Development of a simulation model for the automatic optimization of tools for tube embossing. (August 2019) - Derr, R.; Jung, A.; Diebels, S.
Graphical abstract: Highlights: Simulation of tube embossing with different tool parameters. Influence of batch tolerances on embossing result. Optimization of tool parameters. Multidimensional tube forming by combination of bending and embossing. Abstract: In recent years, the wall thickness of exhaust tubes has been reduced due to lightweight construction, which makes the error-free formability significantly more difficult. Since at the same time the outer diameter has risen, the final assembly has become more complex due to a lack of space, because the exhaust tube is installed as last component in vehicles. Hence, the tube must be adapted to the given conditions. Transverse components or the possibility to access other parts require local clearance at the outer surface of the tube. For this reason the tube is being embossed locally according to the necessary clearance. In this study a simulation tool with a graphical user interface (GUI) for the numerical investigation of tube forming processes was developed. The material parameters for the underlying Finite Element (FE) model were determined by means of tensile tests. The validation of the simulation results was carried out by an experimental adjustment of the embossing process on straight tubes. Based on the obtained results using the FE method, an automated parameter optimization of the embossing settings was implemented to determine the optimal forming configuration.